Hubungan Usia dan Paritas dengan Breastfeeding Self Efficacy pada Ibu Post Partum - Moneca Diah L; Risma Aliviani Putri; Fiktina V (Indonesian Journal of Midwifery (IJM), 2022)
Breastfeeding self efficacy is the self-confidence that mothers have in terms of breastfeeding that can predict whether the mother will decide to breastfeed, how much effort is made to breastfeed, whether to have a constructive or destructive mindset and how to respond to various problems and difficulties during breastfeeding. Research shows that breastfeeding self-efficacy is an important factor associated with the initiation, duration and exclusion of breastfeeding. The purpose of this study was to analyze factors associated with breastfeeding self efficacy in postpartum mothers. The study was conducted at PMB Ignasia Tripuji Astuti, S.ST. Keb, Kandangan Village bawen district of Semarang regency. Research design using analytical surveys with a sample of 30 postpartum mothers. Data analysis with descriptive analysis methods The results of the Chi Square test obtained a p-value of 1,000, because the p-value of 1,000>Î± (0.05), then there was no significant association between maternal age and breastfeeding self efficacy. Chi Square test results obtained a p-value of 0.011. Because of p-value 0.011<Î± (0.05), there is a significant relationship between parity and breastfeeding self efficacy in PMB Ignasia Tripuji Astuti, S.ST. Keb Kandangan Village. The odd ratio is 10.83. This suggests that primipara mothers have a 10.83 times greater risk of having low breastfeeding self efficacy, compared to multipara mothers. The conclusion of this study in maternal age showed no association with breast feeding self efficacy of postpartum mothers while parity showed there was a significant association to breastfeeding self efficacy of postpartum mothers in PMB Ignasia Tripuji Astuti, S.ST. KebAbstrak Breastfeeding self efficacy merupakan keyakinan diri yang dimiliki oleh ibu dalam hal menyusui yang dapat memprediksi apakah ibu akan memutuskan untuk menyusui, sebesar apa upaya yang dilakukan untuk menyusui, apakah mempunyai pola pikir yang membangun atau merusak dan bagaimana cara merespon berbagai masalah dan kesulitan selama menyusui. Penelitian menunjukan bahwa breastfeeding self efficacy adalah faktor penting yang berhubungan dengan inisiasi, durasi dan keeksklusifan menyusui. Tujuan penelitian ini untuk menganalisis faktor yang berhubungan dengan breastfeeding self efficacy pada ibu postpartum. Â Penelitian ini dilaksanakan di PMB Ignasia Tripuji Astuti, S.ST.Keb, Desa Kandangan Kecamatan Bawen Kabupaten Semarang. Desain penelitian menggunakan survei analitik dengan sampel 30 ibu postpartum. Analisis data dengan metode descriptive analysis Â Hasil penelitian didapatkan uji Chi Square diperoleh p-value sebesar 1,000, karena p-value 1,000>Î± (0,05), maka tidak ada hubungan secara signifikan antara umur ibu dengan breastfeeding self efficacy. Hasil uji Chi Square diperoleh p-value sebesar 0,011. Oleh karena p-value 0,011<Î± (0,05), maka ada hubungan secara signifikan antara paritas dengan breastfeeding self efficacydi PMB Ignasia Tripuji Astuti, S.ST.Keb Desa Kandangan. Hasil nilai Odd Rasio diperoleh sebesar 10,83. Ini menunjukkan bahwa ibu primipara memiliki resiko 10,83 kali lebih besar memiliki breastfeeding self efficacy rendah, dibandingkan ibu multipara Simpulan dari penelitian ini usia ibu menunjukkan tidak ada hubungan dengan breast feeding Self Efficacy ibu postpartum sedangkan paritas menunjukan ada hubungan yang signifikan terhadap Breastfeeding Self Efficacy ibu postpartum di PMB Ignasia Tripuji Astuti, S.ST.Keb.